Changes in mitochondrial DNA alter expression of nuclear encoded genes associated with tumorigenesis - Jandova, Jana (2012)
We previously reported the presence of a mtDNA mutation hotspot in UV-induced premalignant and malignant skin tumors in hairless mice. We have modeled this change (9821insA) in murine cybrid cells and demonstrated that this alteration in mtDNA associated with mtBALB haplotype can alter the biochemical characteristics of cybrids and subsequently can contribute to significant changes in their behavioral capabilities. This study shows that changes in mtDNA can produce differences in expression levels of specific nuclear-encoded genes, which are capable of triggering the phenotypes such as seen in malignant cells. From a potential list of differentially expressed genes discovered by microarray analysis, we selected MMP-9 and Col1a1 for further studies. Real-time PCR confirmed up-regulation of MMP-9 and down-regulation of Col1a1 in cybrids harboring the mtDNA associated with the skin tumors. These cybrids also showed significantly increased migration and invasion abilities compared to wild type. The non-specific MMP inhibitor, GM6001, was able to inhibit migratory and invasive abilities of the 9821insA cybrids confirming a critical role of MMPs in cellular motility. Nuclear factor-κB (NF-κB) is a key transcription factor for production of MMPs. An inhibitor of NF-κB activation, Bay11-7082, was able to inhibit the expression of MMP-9 and ultimately decrease migration and invasion of mutant cybrids containing 9821insA. These studies confirm a role of NF-κB in the regulation of MMP-9 expression and through this regulation modulates the migratory and invasive capabilities of cybrids with mutant mtDNA. Enhanced migration and invasion abilities caused by up-regulated MMP-9 may contribute to the tumorigenic phenotypic characteristics of mutant cybrids.